Chemical warfare agent simulants in Gamble’s fluid: Is the fluid toxic? Can it be made safer by inclusion of solid nanocrystalline metal oxides? - Karote, Dennis; Walker, Brandon; Dai, Huaien; Krishnamoorthi, Ramaswamy; Voo, Janis; Rajagopalan, Shyamala (My University, 2012)
The reactions of chemical warfare agent simulants, 2-chloroethyl ethyl sulfide (2-CEES) and di-i-propyl fluoro phosphate (DFP), in fluids have been investigated. Data analyses confirm the major degradation pathway to be hydrolysis of 2-CEES to 2-hydroxyethyl ethyl sulfide, along with minor self-condensation products. Among the three fluids examined, 2-CEES degradation was the fastest in Gamble’s fluid during a 96 h period. Upon addition of Exceptional Hazard Attenuation Materials (EHAMs) to 2-CEES containing Gamble’s fluid, degradation was generally improved during the first 24 h period. The 96 h outcome was similar for fluid samples with or without EHAM 2 and EHAM 4. EHAM 1-added fluid contained only one degradation product, 2-nitroethyl ethyl sulfide. DFP degradation was the slowest in Gamble’s fluid, but was enhanced by the addition of EHAMs. FTIR and solid state 31P NMR confirm the destructive adsorption of 2-CEES and DFP by the EHAMs. The results collectively demonstrate that 2-CEES and DFP decompose to various extents in Gamble’s fluid over a 96 h period but the fluid still contains a considerable amount of intact simulant. EHAM 1 appears to be promising for 2-CEES and DFP mitigation while EHAM 2 and EHAM 4 work well for early on concentration reduction of 2-CEES and DFP.
Citation: Karote, Dennis, Brandon Walker, Huaien Dai, Ramaswamy Krishnamoorthi, Janis Voo, and Shyamala Rajagopalan. “Chemical Warfare Agent Simulants in Gamble’s Fluid: Is the Fluid Toxic? Can It Be Made Safer by Inclusion of Solid Nanocrystalline Metal Oxides?” Edited by Meehir Palit. Journal of Chemistry 2013 (December 5, 2012): 641620. https://doi.org/10.1155/2013/641620.
Keywords: Chemical warfare; Gamble’s fluid; 2-chloroethyl ethyl sulfide; di-i-propyl fluoro phosphate; Exceptional Hazard Attenuation Materials